Evaluation of Target Attainment of Vancomycin Area Under the Curve in Children With Methicillin-Resistant Staphylococcus Aureus Bacteremia. Issue 5 (October 2015) - Hahn, Andrea; Frenck, Robert W.; Allen-Staat, Mary; Zou, Yuanshu; Vinks, Alexander A.
Abstract : Background: Vancomycin is often required to treat methicillin-resistant Staphylococcus aureus bacteremia in children. Treatment failure occurs in up to 50% of adults and is associated with a 24-hour area under the curve/minimum inhibitory concentration (AUC24h /MIC) <400. We sought to identify patient factors associated with vancomycin AUC and whether AUC24h /MIC <400 was predictive of treatment failure in children. Methods: Hospitalized children younger than 18 years with methicillin-resistant Staphylococcus aureus bacteremia receiving vancomycin were included in a retrospective cohort study. AUC24h was calculated using a validated pharmacokinetic model. Factors such as age, sex, underlying conditions, presence of foreign bodies, patient site of infection, and markers of illness severity were examined for an association with vancomycin AUC, and AUC24h /MIC was evaluated for an association with treatment failure. Results: Subjects requiring intensive care unit support were significantly more likely to have higher vancomycin AUC24h and AUCavg than those subjects not needing intensive care unit support. Although vancomycin serum trough concentrations are predictive of vancomycin AUC, suboptimal exposure of vancomycin occurred in almost 20% of subjects despite trough concentrations within the target range. A relationship between vancomycin AUC24h /MIC and treatment failure could not be established. Conclusions: To ensure optimal AUC/MIC pharmacodynamic index, especially in critically ill patients, estimation of the AUC is critical.